Modelling and projections of the COVID-19 epidemic and the potential impact of social distancing in Cameroon - Solange W. Youdom; Henri E.Z. Tonnang; Simeon P. Choukem (AOSIS, 2021)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) disease (COVID-19) pandemic continues to be a global health problem with a significant impact in Cameroon. The aim of this study was to improve the understanding of the spread of COVID-19 and enhance disease control strategies. We assessed the SIRD (susceptible, infected, recovered and death) model to describe COVID-19 reported cases in Cameroon from March 7 to May 31, 2020, and study the impact of social distancing. We assessed changes in the basic reproduction number (R0) on a phaseadjusted process and forecasted the longterm epidemic trend. Daily incidence data was fitted to a log-linear model before each peak of the epidemic with the purpose of studying the effective mechanism of variation of the reproduction number Re. Before the first peak of the epidemic, R0 was estimated as 6.8. Social distancing and restricted measures contributed to reduce the value to 3.24 by April 30 but remained greater than 1 (R0=2.43) by May 22 when the initial measures implemented by the government to control the spread of the disease were relaxed. The estimated number of infections ranged 13,703-18,456 by May 31, and will continue increasing throughout June 2020 with more than 20,000 cases expected by the end of June 2020, suggesting that the pandemic is still in the growth phase. Longterm prediction showed a flattened curve towards April 2021. Preventive measures initially implemented by the government of Cameroon should be strictly maintained and reinforced to reduce Re to 0.5.